Direct methods for the approximate solution of systems of singular integral equations in the case of nonnegative partial indices - Malyshev, К. I. (Ukrains’kyi Matematychnyi Zhurnal, 1999)
We justify direct methods for the approximate solution of systems of singular integral equations with Cauchy kernel on a unit circle in the case of nonnegative partial indices.